2018
DOI: 10.1111/bcp.13725
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring of small molecule kinase inhibitors in oncology in a real‐world cohort study: does age matter?

Abstract: In this real-world study, exposure to most included KIs was comparable in older and younger patients, except for dabrafenib, which showed higher exposure in older patients. In the absence of an absolute target for this KI, clinical relevance remains unclear. For all other included KIs, our data suggest no clinically relevant influence of older age on KI exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Age is an important factor that influences imatinib concentration, and is a risk factor in imatinib mesylate cardiotoxicity, which suggests that age is an important factor in patients with CML treated with imatinib. A real‐world cohort study confirmed that age could change the concentration of small‐molecule kinase inhibitors (such as imatinib) in patients with CML 35 . In this study, we found a significant negative correlation between age and blood concentration of imatinib, and age could also reduce the concentrations of its metabolites.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Age is an important factor that influences imatinib concentration, and is a risk factor in imatinib mesylate cardiotoxicity, which suggests that age is an important factor in patients with CML treated with imatinib. A real‐world cohort study confirmed that age could change the concentration of small‐molecule kinase inhibitors (such as imatinib) in patients with CML 35 . In this study, we found a significant negative correlation between age and blood concentration of imatinib, and age could also reduce the concentrations of its metabolites.…”
Section: Discussionsupporting
confidence: 72%
“…A real-world cohort study confirmed that age could change the concentration of small-molecule kinase inhibitors (such as imatinib) in patients with CML. 35 In this study, we found a significant negative correlation between age and blood concentration of imatinib, and age could also reduce the concentrations of its metabolites. At the same time, the serum imatinib C trough concentrations in patients with CML aged 17-47 and 48-68 years (1374 and 1218 ng/mL) were significantly reduced, compared with the group aged 7-16 years.…”
Section: Distinct Individual Differences In Imatinib Use Of CML Patientssupporting
confidence: 52%
“…In a real-world cohort study (454 patients), comparing tyrosine kinase inhibitors exposed to two age groups (<70 years and ≥70 years) only dabrafenib showed significantly higher exposure in older patients. Conversely, erlotinib, imatinib, pazopanib, sunitinib and vemurafenib exposure was not affected by age of patients [28]. Importantly, one third of total patients did not reach the proposed target concentration of their tyrosine kinase inhibitor, indicating that individual drug monitoring may improve cancer therapy independent of age.…”
Section: Genetic Polymorphisms and Therapeutic Drug Monitoringmentioning
confidence: 92%
“…67 The blood concentration of SU fluctuates slightly between different ages, but a study shows that the exposure dose of mRCC patients over the age of 70 is significantly lower than that of young patients. 68 There is no difference in the metabolism of IM between patients with normal or abnormal liver function, but it is recommended that the maximum dose of mild liver dysfunction is 500mg/d, 69 and a small range of GIST liver metastasis will not affect the metabolism of IM. About 50% of the patients in the outpatient follow-up are unable to reach effective drug concentrations, and there is a risk of treatment failure or drug resistance, while about 5% of the patients' blood concentrations are higher than 2000ng/mL, and their AST, ALT levels are all elevated, which may be related to liver metabolic disorders.…”
Section: Metabolic Related Factorsmentioning
confidence: 99%
“…79 A study have shown that there is no significant difference in blood concentration between the elderly and non-elderly patients with the same dose of IM. 68 A preclinical experiment has shown that hypoproteinemia may lead to a decrease in the total concentration of SU and N-desethylsunitinib as well as increasing the distribution. 37 The fluctuation of blood concentration in GIST patients with is related to race, lifestyle and other factors, and this uncertainty needs to be confirmed by more real-world studies.…”
Section: Other Related Factorsmentioning
confidence: 99%